AB0461 Long-term use of adalimumab as monotherapy following attainment of low-disease activity: Subanalysis of the open-label extension of premier. (23rd January 2014) - Keystone, E.C.; Breedveld, F.C.; Kupper, H.; Liu, S.; Florentinus, S.
Abstract : Background: There has been increased interest in understanding whether biologics can be safely withdrawn from patients (pts) receiving combination therapy with MTX once a clinical target has been achieved. The ability of the biologic to maintain the target as monotherapy has received less consideration. Objectives: To evaluate long-term clinical and radiographic outcomes in pts treated with open-label (OL) adalimumab (ADA) as monotherapy following attainment of low-disease activity (LDA). Methods: PREMIER was a 2-year (yr), phase 3, randomized, controlled trial (RCT) in MTX-naïve pts with early RA who were randomized to MTX, ADA (40 mg every other week), or ADA+MTX. 1 Pts completing the RCT were eligible to receive OL ADA for up to an additional 8 yrs (this trial is ongoing); MTX could be added at the investigator's discretion. This post hoc analysis included data from pts who were in an LDA state [defined as DAS28(CRP) <3.2] at Yr 2 (ie, the end of the RCT) and received OL ADA as monotherapy between Yrs 2 and 8. The percentages of pts remaining in LDA at Yr 8 were summarized using non-responder imputation (NRI) based on the population entering the OL period and as observed for pts with clinical and radiographic data available at Yrs 2 and 8. The mean ΔmTSS from Yr 2 to Yr 8 and the percentage of pts without radiographic progression (ΔmTSS ≤0.5) from Yr 2 to Yr 8 were summarized. Results: Of the 497 pts who enrolled in the OL extension, 313 were in an LDA state at the end of the RCT (ie, Yr 2). Among the LDA responders, 173 (55%) received ADA as monotherapy during the OL period. One-half (n/N=87/173, 50%) of the pts who entered the OL period with LDA maintained this disease activity state at Yr 8 with ADA monotherapy (Table). More than half (n/N=99/173, 57%) completed 6 yrs of OL ADA monotherapy and had DAS28(CRP) values at Yr 8, with 88% (n/N=87/99) maintaining LDA at the Yr 8 assessment. Further, OL ADA monotherapy was associated with clinically insignificant radiographic progression for pts completing Yr 8 (annual progression rate between Yrs 2 and 8, ΔmTSS =0.4 units/yr). Conclusions: OL ADA effectively maintained pts in a state of LDA and with minimal radiographic progression following 6 yrs of treatment. These data suggest that ADA monotherapy can be effective in some pts whose disease activity does not necessitate supplemental MTX therapy. References: Breedveld FC, et al. Arthritis Rheum 2006;54:26-37. Disclosure of Interest: E. Keystone Grant/Research support from: Abbott, AstraZeneca, Biotest, BMS, Centocor, Genentech, Merck, Nycomed, Pfizer, Roche, UCB, Consultant for: Abbott, Amgen, AstraZeneca, BMS, Centocor, Genzyme, Merck, Novartis, Pfizer, UCB, F. Breedveld Consultant for: Centocor, Schering-Plough, Amgen/Wyeth, Abbott, H. Kupper Shareholder of: Abbott, Employee of: Abbott, S. Liu Shareholder of: Abbott, Employee of: Abbott, S. Florentinus Shareholder of: Abbott, Employee of: Abbott